DAMPAK IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL DAN PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN ROTE NDAO - Tuati, Nonce Farida; Manuain, Deetje Wieske; Sir, Jennie Sarlota (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2025)
This study aims to understand the implementation of accrual-based accounting and internal control and its impact on the quality of financial statements. It is hoped that the results of this research can contribute to the development of accounting science and become a reference for public sector organizations in Indonesia, such as the government, universities, central and regional public service agencies, as well as other business and social organizations. The research sample is Regional Financial Management officials in all regional apparatus organizations in the Rote Ndao Regency Government who are responsible for the management of the APBD to the preparation of financial statements. The sampling technique uses purposive sampling. The data used is primary data collected through questionnaires that are distributed directly to respondents. The analysis was carried out using a multiple regression model to test the hypothesis through the t-test and the F-test. Simultaneously, the application of accrual-based accounting and internal control also has a significant influence on the quality of financial statements, supporting the acceptance of hypotheses.